math.com
Home    |    Teacher    |    Parents    |    Glossary    |    About Us
Homework Help Practice Ask An Expert Calculators & Tools Games Store
Email this page to a friend Email this page to a friend
Resources
· Cool Tools
· Formulas & Tables
· References
· Test Preparation
· Study Tips
· Wonders of Math
 
Search
Custom Search



Math Jobs


  
Chain Rule
(Math | Calculus | Derivatives | Identities | Chain Rule)
(d/dx) f(g(x)) = (d/dg) f(g) * (d/dx) g(x)


Proof of (d/dx) f(g(x)) = (d/dg) f(g) * (d/dx) g(x) from the definition

We can use the definition of the derivative:

(d/dx) f(x) = lim
d-->0  
f(x+d)-f(x)
d
Therefore, (d/dx) f(g(x)) can be written as such:
(d/dx) f(g(x)) = df/dx = (f(g(x+d) - f(g(x))/d
df/dx * 1/(dg/dx) = [ (f(g(x+d) - f(g(x))/d ] * [ d/(g(x+d) - g(x)) ]
= ( f(g(x+d))-f(g(x)) )/(g(x+d)-g(x)) = df/dg
df/dx = df/dg * dg/dx


  
 
  

 
Contact us | Advertising & Sponsorship | Partnership | Link to us

© 2000-2005 Math.com. All rights reserved.     Legal Notices.     Please read our Privacy Policy.